O'Reilly Book Club. (O'Reilly Media, Inc., 2023)
Join us for this edition of O'Reilly Book Club with Aurélien Géron, author of Hands-On Machine Learning with Scikit-Learn, Keras, and TensorFlow, to learn about the fundamentals of machine learning. You'll cover everything from working with real data to training and deploying models as you learn tricks of the trade, listen to stories, ask your questions, and connect with other readers. What you'll learn and how you can apply it Learn the concepts, tools, and techniques for doing end-to-end machine learning Explore the latest deep learning technologies, such as vision transformers, multimodal models, and more Find out how to update your machine learning systems for state-of-the-art performance This recording of a live event is for you because... You want to go beyond the words on the page and hear from the expert. You're a machine learning practitioner who wants to learn about the latest developments in the field, including updates to scikit-learn and Keras, large language models, and new generative learning tools such as diffusion models. Recommended follow-up: Read Hands-On Machine Learning with Scikit-Learn, Keras, and TensorFlow, third edition (book) Watch Natural Language Processing Using Transformer Architectures (video) Read TensorFlow 2 Pocket Reference (book).